1999
DOI: 10.1117/12.341274
|View full text |Cite
|
Sign up to set email alerts
|

Micro-EDM for silicon microstructure fabrication

Abstract: Currently, most silicon microstructures used in microsystems are produced by photolithographic methods. The reason for this is the well-developed etching technology, used in microelectronics, that has been transferred to the microsystem domain. But since the making of an arbitrary shape or angle on silicon mainly depends on the crystal orientation, some severe limits exist in the production of three-dimensional structures.Electro-Discharge Machining (EDM) is basically a thermal process. During the 11DM process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…This machine can operate with a 150 μm diameter electrode. There is also the possibility to locally reduce the diameter of the electrode using a wire system integrated into the machine [7,8]. In that way the diameter can be reduced down to 50 μm.…”
Section: Micro Edmmentioning
confidence: 99%
“…This machine can operate with a 150 μm diameter electrode. There is also the possibility to locally reduce the diameter of the electrode using a wire system integrated into the machine [7,8]. In that way the diameter can be reduced down to 50 μm.…”
Section: Micro Edmmentioning
confidence: 99%
“…The polarity of workpiece electrode was kept positive in the experiments. It was found that when sparking energy level was more than 10 mJ, more and quite larger micro cracks would be induced in the machined surface of silicon [28]. Therefore, capacitance and open circuit voltage were determined as 220 pF and 60 V, respectively, considering the drilling experiments could be conducted under relatively low discharge energy.…”
Section: Methodsmentioning
confidence: 99%
“…Here, a modified version of the heat-shrink based interconnections developed by Pan et al [9] has been incorporated in the cylinder wall. The interconnections developed here operate as follows (see figure 8): A tube with a flange is fabricated in the cylinder wall by µEDM with WireElectro-Discharge-Grinding (WEDG) [10] formed electrodes. Next a micro heat shrink tube [11] is placed over the flange, which is then heated until the heat-shrink tube is enveloping it.…”
Section: Manufacturing Of Fluidic Microactuatorsmentioning
confidence: 99%